2023
DOI: 10.1038/s41380-023-02340-4
|View full text |Cite
|
Sign up to set email alerts
|

Retina as a potential biomarker in schizophrenia spectrum disorders: a systematic review and meta-analysis of optical coherence tomography and electroretinography

Hiroshi Komatsu,
Goh Onoguchi,
Steven M. Silverstein
et al.

Abstract: Introduction Abnormal findings on optical coherence tomography (OCT) and electroretinography (ERG) have been reported in participants with schizophrenia spectrum disorders (SSDs). This study aims to reveal the pooled standard mean difference (SMD) in retinal parameters on OCT and ERG among participants with SSDs and healthy controls and their association with demographic characteristics, clinical symptoms, smoking, diabetes mellitus, and hypertension. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 204 publications
1
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to explore the association between genetic risk for schizophrenia and retinal variations within a large population-based sample using the latest GWAS. 11 Moreover, our results extend prior findings of retinal thinning in patients with schizophrenia compared to healthy individuals, 4,5,8,9,37 demonstrating an association between genetic risk for schizophrenia and these retinal phenotypes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to explore the association between genetic risk for schizophrenia and retinal variations within a large population-based sample using the latest GWAS. 11 Moreover, our results extend prior findings of retinal thinning in patients with schizophrenia compared to healthy individuals, 4,5,8,9,37 demonstrating an association between genetic risk for schizophrenia and these retinal phenotypes.…”
Section: Discussionsupporting
confidence: 80%
“…29 In the current study, we focused on the macula as it contains mutiple layers that based on prior investigations show thinning in individuals diagnosed with schizophrenia. 9,30,31…”
Section: Methodsmentioning
confidence: 99%
“…7 Another systematic review looked at studies which have reported retinal abnormalities using optical coherence tomography and electroretinography among schizophrenia spectrum patients. 8 This review reported that the retinal changes in these patients can be both trait and state markers. Eye-tracking studies offer an opportunity to understand oculomotor functioning which correlates with various aspects of brain functioning.…”
Section: Introductionmentioning
confidence: 99%